Sports doping in the adolescent: the Faustian conundrum of Hors De Combat - Greydanus, D. E.; Patel, D. R. (Pediatric Clinics of North America, 2010)
The drive toward success in sports and the need for a cosmetically acceptable appearance have driven many adolescents to take a wide variety of so-called doping substances. The consumption of these chemicals in the hope and hype of improved sports performance, fueled by the easing of government restrictions on their proof of safety and efficacy, has resulted in an explosion of so-called ergogenic products available to our youth. Agents that have been used include anabolic steroids, anabolic-like agents, designer steroids, creatine, protein and amino acid supplements, minerals, antioxidants, stimulants, blood doping, erythropoietin, ß-blockers, and others. The use of these agents has considerable potential to cause physical and psychological damage. Use and misuse of drugs in this sports doping process should be discouraged. This discussion reviews some of the agents that are currently being used. Clinicians providing sports medicine care to youth, whether through anticipatory guidance or direct sports medicine management, should educate their young patients about the hype and hyperbole of these products that may keep them out instead of in the game at considerable financial cost to the unwary consumer.